Ectopic expression of AtDGAT1, encoding diacylglycerol O-acyltransferase exclusively committed to TAG biosynthesis, enhances oil accumulation in seeds and leaves of Jatropha. Issue 1 (December 2016) - Maravi, Devendra; Kumar, Sanjeev; Sharma, Prabin; Kobayashi, Yasufumi; Goud, Vaibhav; Sakurai, Nozomu; Koyama, Hiroyuki; Sahoo, Lingaraj
Abstract Background Jatropha curcas is an important biofuel crop due to the presence of high amount of oil in its seeds suitable for biodiesel production. Triacylglycerols (TAGs) are the most abundant form of storage oil in plants. DiacylglycerolO -acyltransferase (DGAT1) enzyme is responsible for the last and only committed step in seed TAG biosynthesis. Direct upregulation of TAG biosynthesis in seeds and vegetative tissues through overexpression of theDGAT1 could enhance the energy density of the biomass, making significant impact on biofuel production. Results The enzyme diacylglycerolO -acyltransferase is the rate-limiting enzyme responsible for the TAG biosynthesis in seeds. We generated transgenic Jatropha ectopically expressing anArabidopsis DGAT1 gene throughAgrobacterium -mediated transformation. The resultingAtDGAT1 transgenic plants showed a dramatic increase in lipid content by 1.5- to 2 fold in leaves and 20–30 % in seeds, and an overall increase in TAG and DAG, and lower free fatty acid (FFA) levels compared to the wild-type plants. The increase in oil content in transgenic plants is accompanied with increase in average plant height, seeds per tree, average 100-seed weight, and seed length and breadth. The enhanced TAG accumulation in transgenic plants had no penalty on the growth rates, growth patterns, leaf number, and leaf size of plants. Conclusions In this study, we produced transgenic Jatropha ectopically expressingAtDGAT1 . We successfully increased the oil content by 20–30 % in seeds and 1.5- to 2.0-fold in leaves of Jatropha through genetic engineering. Transgenic plants had reduced FFA content compared with control plants. Our strategy of increasing energy density by enhancing oil accumulation in both seeds and leaves in Jatropha would make it economically more sustainable for biofuel production.